IS ECONOMIC GROWTH AND INDUSTRIAL GROWTH THE REASON FOR ENVIRONMENTAL DEGRADATION IN SAARC COUNTRIES - Jadoon, Atif Khan; Akhtar, Sania; Sarwar, Ambreen; Batool, Syeda Azra; Chatrath, Sarvjeet Kaur; Liaqat, Saima (International Journal of Energy Economics and Policy, 2021)
In the last four decades, the developing countries have built a heavy industrial base which is seen as a threat to the environment. The trade liberalization policies of the SAARC counties led them to increase the production for domestic use and exports. This increase in industrial output is a real threat to environmental degradation as the industrial share is quite significant in the GDP of the SAARC countries. The present study is designed to check the existence of the Environmental Kuznets Curve (EKC) hypothesis and then use industry output as a regressor to see how it is affecting the environment. The panel regression models are used for estimation by taking data from 1980 to 2018. The results are obtained by using Newey-West standard robust errors. The results suggested that there exists a U-shape relationship between economic growth and Carbon Dioxide (CO2) while an inverted U-shape relationship is found between industrial growth and CO2. Furthermore, a unidirectional causality was observed between industrial growth, human capital, energy consumption, and CO2 while bidirectional causality was observed between urbanization and CO2. The present study suggests that there is a need to adopt environmental protection policies related to the industrial sector in the SAARC region. Keywords: Economic Growth, Idustrial Growth, Environmental Degradation JEL Classifications: Q43, Q54, R11 DOI: https://doi.org/10.32479/ijeep.11769